2022
DOI: 10.1002/ijc.34204
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to SARS‐Cov‐2 infection and risk for severe COVID‐19 in patients with prostate cancer on androgen deprivation therapy

Abstract: Androgen deprivation therapy (ADT) has been hypothesized to protect against COVID‐19, but previous observational studies of men with prostate cancer on ADT have been inconsistent regarding mortality risk from coronavirus disease 2019 (COVID‐19). Using data from the Prostate Cancer data Base Sweden (PCBaSe), we identified a cohort of 114 547 men with prevalent prostate cancer on the start of follow‐up in February 2020, and followed them until 16 December 2020 to evaluate the association between ADT and time to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Considering the risk of subsequent hospital admission or death, these results were even higher (OR, 1.4; 95% CI: 1.0-1.9). Again, these data seem to disprove the protective role of ADT in preventing SARS-CoV-2 infection and its sequelae, enforcing data from another smaller Swedish case-control analysis [58,86].…”
Section: Retrospective Studiesmentioning
confidence: 68%
See 1 more Smart Citation
“…Considering the risk of subsequent hospital admission or death, these results were even higher (OR, 1.4; 95% CI: 1.0-1.9). Again, these data seem to disprove the protective role of ADT in preventing SARS-CoV-2 infection and its sequelae, enforcing data from another smaller Swedish case-control analysis [58,86].…”
Section: Retrospective Studiesmentioning
confidence: 68%
“…Similarly, abiraterone acetate, a selective inhibitor of the enzyme 17αhydroxylase/C17,20-lyase (CYP17) and a partial antagonist of AR, has been evaluated as an anti-SARS-CoV-2 therapy: in vitro results suggested that abiraterone might reduce the size of viral plaques and decrease N and S viral protein production [56]. Subsequent in vivo studies later disproved these results and abiraterone has consequently not been employed as an anti-viral treatment [57][58][59]. The effect of apalutamide, an oral competitive signaling inhibitor of the ligand-binding domain of the androgen receptor, on SARS-CoV-2 infection has also been tested by in vitro studies with Calu-3 lung adenocarcinoma cells and primary human nasal epithelial cells, finding a reduction in SARS-CoV-2 entry [6].…”
Section: Androgen Deprivation Therapymentioning
confidence: 99%
“…Thus, ADT may have a protective effect, decreasing the severity of COVID-19 in PCa patients [ 40 ]. However, other clinical studies obtained discordant results and the role of ADT in reducing COVID-19 infection severity in men is still a matter of debate [ 41 , 42 , 43 , 44 , 45 , 46 ]. Particularly, recent studies have shown that PCa patients under ADT treatment presented a higher risk of contracting COVID-19 and hospital admission [ 44 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other clinical studies obtained discordant results and the role of ADT in reducing COVID-19 infection severity in men is still a matter of debate [ 41 , 42 , 43 , 44 , 45 , 46 ]. Particularly, recent studies have shown that PCa patients under ADT treatment presented a higher risk of contracting COVID-19 and hospital admission [ 44 , 47 ]. Still, Schmidt et al noted no association between ADT treatment and 30-day mortality among patients with PCa and COVID-19 [ 43 ].…”
Section: Discussionmentioning
confidence: 99%